A unique exceptionally well-preserved pterosaur skull from the Crato Formation of Brazil - Campos,Hebert Bruno Nascimento; Cincotta,Aude; Frey,Eberhard; Godefroit,Pascoal; Yans,Johan (PeerJ Preprints, 2017)
The posterior part of a skull from a tapejarid pterosaur was studied for the exceptional preservation of its soft-tissues. The specimen comes from the Early Cretaceous (Aptian) Crato Formation of northeastern Brazil. It shows a peculiar soft sagittal crest that gives new information about the anatomy and the diversity of tapejarids. The specimen lies on five limestone slabs. The bony part comprised the posterior part of the skull, with the braincase and one complex of three dorsally oriented and associated bony crests. The crest consists of a huge and elongated parietal crest, a trabecular frontal crest, and an occipital spine. The specimen preserves the posterior parts of the nasoantorbital fenestra and orbit. The soft cranial crest is characterized by a multilinear dorsal crest with almost parallel fibres, which curve posteriorly. Pigment organelles – melanosomes – were observed in the crest as well as ‘hair-like’ fibres (pycnofibres). They present diverse shapes and sizes, suggesting diverse colorations for the soft tissues. The new tapejarid shares certain features with the tapejarids Tupandactylus imperator and “Huaxiapterus” benxiensis, which include an elongated parieto-occipital crest. Nonetheless, it differs from Tupandactylus imperator and Ingridia navigans by the following characteristics: absence of a suprapremaxillary spine, very dorsally oriented posterior crests, as well as a specific morphology for the soft crest. Our specimen can therefore be assigned to a new taxon of Tapejaridae, a group previously reported from the Crato Formation.
Keywords: Tapejaridae; Pterosauria; Pterodactyloidea; Crato Formation; Early Cretaceous